Search for supersymmetry via associated production of charginos and neutralinos in final states with three leptons - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2005)
A search for associated production of charginos and neutralinos is performed using data recorded with the D0 detector at a p (p) over bar center-of-mass energy of 1.96 TeV at the Fermilab Tevatron Collider. This analysis considers final states with missing transverse energy and three charged leptons, of which at least two are electrons or muons. No evidence for supersymmetry is found in a data set corresponding to an integrated luminosity of 320 pb(-1). Limits on the product of the production cross section and leptonic branching fraction are set. For the minimal supergravity model, a chargino lower mass limit of 117 GeV at the 95% C.L. is derived in regions of parameter space with enhanced leptonic branching fractions.